Brane-localized gravity - Mannheim, Philip D. (World Scientific, 2005)
This timely and valuable book provides a detailed pedagogical introduction and treatment of the brane-localized gravity program of Randall and Sundrum, in which gravitational signals are able to localize around our four-dimensional world in the event that it is a brane embedded in an infinitely-sized, higher dimensional anti-de Sitter bulk space. A completely self-contained development of the material needed for brane-world studies is provided for both students and workers in the field, with a significant amount of the material being previously unpublished. Particular attention is given to iss.